2022
DOI: 10.1051/0004-6361/202244514
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton and SRG/eROSITA observations of the isolated neutron star candidate 4XMM J022141.5−735632

Abstract: We report the results of follow-up investigations of a possible new thermally emitting isolated neutron star (INS), 4XMM J022141.5-735632, using observations from XMM-Newton and Spectrum Roentgen Gamma (SRG) eROSITA. The analysis is complemented by Legacy Survey imaging in the optical and near-infrared wavelengths. The X-ray source, the first to be targeted by XMM-Newton in an effort to identify new INS candidates from the fourth generation of the XMM-Newton serendipitous source catalogue Data Release 9 (4XMM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Again, the spin period (18.6 ms) does not fit the M7 family [81]. Finally, the latest discovery is the source 4XMM J022141.5-735632 [82], which for this object, the spin period has not yet been reported.…”
Section: Magnificent Sevenmentioning
confidence: 88%
“…Again, the spin period (18.6 ms) does not fit the M7 family [81]. Finally, the latest discovery is the source 4XMM J022141.5-735632 [82], which for this object, the spin period has not yet been reported.…”
Section: Magnificent Sevenmentioning
confidence: 88%
“…This could be caused by an unfavorable orientation of the rotation and magnetic axes, or by the intrinsic lack, or faintness, of non-thermal magnetospheric emission. The most promising INS candidates are 2XMM J104608.7−594306 [94,95], 4XMM J022141.5−735632 [96,97], eRASSU J065715.3+260428 and eRASSU J131716.9−402647 [98], but with the data release of the first eROSITA catalog we expect a significant enlargement of the sample [99,100]. [105,106].…”
Section: Pos(multif2023)055mentioning
confidence: 95%
“…The RASS Faint Source Catalogue (RASS-FSC) extension includes even more sources with detection likelihoods as low as 7 and a source count minimum of 6 (Voges et al 2000). Since the mid-2000s, there have been five additional XINS discoveries: one from within the 1RXS catalog (Rutledge et al 2008), one from within the 2XMMp catalog (Pires & Motch 2008;Pires et al 2009aPires et al , 2009bPires et al , 2015, and three that were found even more recently using data from either eROSITA in conjunction with the 4XMM-DR9 catalog (Pires et al 2022) or from eROSITA alone (Kurpas et al 2023). A list of the currently known radioquiet isolated neutron stars that emit strongly in X-rays is provided in Table 1, the final column of which will be discussed below in Section 2.…”
Section: Searching For Xinss: a Brief History And Motivationmentioning
confidence: 99%